1977
DOI: 10.1139/v77-190
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nor-anatoxin-a and anatoxin-a

Abstract: The neuro-muscular post-synaptic depolarizing agent anatoxin-a from Anabaena flos-aquae (Lyngb.) de Bréb. has been synthesized from cocaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(19 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…Successful syntheses of analogues specific to neuronal subtypes could be of great value in the treatment of various neurological dysfunctions. The unique structure of anatoxin-a, and its powerful activity as a pharmacological tool, inspired a multitude of chemical synthetic pathways for anatoxin-a and its analogues [25]. The naturally occurring enantiomer, (+)-anatoxin-a, is much more potent than (-)-anatoxin-a [26].…”
Section: Anatoxinsmentioning
confidence: 99%
“…Successful syntheses of analogues specific to neuronal subtypes could be of great value in the treatment of various neurological dysfunctions. The unique structure of anatoxin-a, and its powerful activity as a pharmacological tool, inspired a multitude of chemical synthetic pathways for anatoxin-a and its analogues [25]. The naturally occurring enantiomer, (+)-anatoxin-a, is much more potent than (-)-anatoxin-a [26].…”
Section: Anatoxinsmentioning
confidence: 99%
“…A synthesis of anatoxin-a from cocaine has now been achieved, colifirmillg both the structure and absolute stereochernistry (16). The activity of the toxin as a post-synaptic depolarizing ileurornuscular biocking agent has beell reported (17).…”
Section: Properties and Structurementioning
confidence: 99%
“…By spectra and crystallographic analysis (Huber, 1972;Devlin et al, 1977) and chemical synthesis (Campbell et al, 1977), anatoxin-a was confirmed to be an alkaloid of 2-acetyl-9-azabicyclo[4.2.1]non-2-ene and resembles acetylcholine in its structure. Further studies revealed that anatoxin-a acts as a potent postsynaptic depolarizing neuromuscular blocking agent by binding to the nicotinic acetylcholine receptors (Carmichael et al, 1975(Carmichael et al, , 1979Aronstam and Witkop, 1981).…”
Section: Introductionmentioning
confidence: 99%